Causativity And Alternation Me-Kan /-I In Indonesian - Masreng, Robert; Beratha, N.L., Sutjiati; Sudipa, I Nengah; Darma Laksana, I Ketut (e-Journal of Linguistics; Vol 13 No 1 (2019): e-jl-January, 2019)
Language study is a way of expressing various language phenomena based on macrolinguistics and microlinguistics point of view. The study of macrolinguistic aspects focuses on languages ??relating to other disciplines. On the contrary, microlinguistic study focuses more on language structures, such as phonology, morphology, syntax, and semantics. In this paper, the analysis focuses on the aspect of the Indonesian typology phenomenon from the ponit of view of valence verb of transitive verb based on verb formation process meng-kan/i . The analysis results describe that verbs with affix me-i/-kan form causative construction of both formal and semantic parameters; Verb alternation with affix me-i/-kan can be applied when verbal construction presents locative and benefactive roles in two different constructions; The alternation occurs because it is tied to grammatical relation constructing a clause construction; and the alternation of meng/i raises the verb's valence level in the clause construction.